Nitrogeneous compound fertilizer - Azizah, Shaaban; Se, Sian Meng; Mohd Fairuz, Dimin; Nona Mery Merpati, Mitan (2014)
The present invention relates to a fertilizer for plant comprising urea and biochar, said urea is impregnated onto the biochar, wherein the urea is slowly released to the surrounding releasing nitrogen for uptake by the plant. One advantage of the urea impregnated biochar fertilizer is that it retains more nitrogen nutrients such as ammonium (NH4+), nitrate (NO3-) and N-urea in soil. The urea impregnated biochar fertilizer also reduces potential emission.